Post-marketing safety surveillance study of a 9-valent human papillomavirus vaccine in individuals aged 16-26 years in Chongqing, China - Yuan-yuan Zhang; Jia-Wei Xu; Yang Liu; Wei Qiu; Pei-Ning Bai; Yi Zeng; Qing Wang (Taylor & Francis Group, 2023)
ABSTRACTThe safety of human papillomavirus (HPV) vaccines, one of the major challenges to public vaccination, has been controversial. This study assessed the adverse reactions of 9-valent HPV (9vHPV) vaccines. This open-label, observational, multi-center, post-marketing study assessed the safety of 9vHPV administered according to local clinical practice. All post-marketing adverse events (AEs) reports received between December 2019 and November 2021 in Chongqing were analyzed. A total of 1000 individuals aged 16-26 years provided safety data post-vaccination; The most common AEs (60.1%) experienced by 9vHPV vaccine recipients were vaccination-site AEs (pain, swelling, induration) and non-vaccination-site AEs (dizzy, weak, fever). Vaccination-site AEs most were mild-to-moderate in intensity. Discontinuations and HPV 9-related serious AEs were rare (0.3% and 0.0%, respectively). Eight SAEs were reported during the study but none were considered as related to the study vaccine. The 9vHPV vaccine was generally well tolerated in subjects aged 16-26 years; Vaccination-site AEs were more common with 9vHPV.